2020
DOI: 10.1111/jopr.13171
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Distribution of Image Matched Fiducial Markers on Accuracy of Computer‐Guided Implant Surgery

Abstract: PurposeImage registration of the optical intraoral scan to computed tomography image is essential for computer‐guided implant surgery. The remaining teeth, which are considered to be congruent structures observed in the scan and radiographic images, are used to perform the image registration. The purpose of this study was to evaluate the effects of the distribution of matching fiducial points on the accuracy of the image registration.Materials and MethodsA partially edentulous model with three anterior remaini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…The surface-based matching uses the computer algorithm of iterative closest points (ICPs) that locates paired images in optimal positions by computing the 3D coordinates of the geometrical shape of 3D object surfaces to align images [17,22]. When the image surface point clouds that are used for matching are widely spread in the oral cavity, the matching condition is favorable, and the whole accuracy of image registration can be increased [15,33]. In the present study, a significant correlation was found between the threshold of gray value factor and the number of remaining teeth on the registration accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…The surface-based matching uses the computer algorithm of iterative closest points (ICPs) that locates paired images in optimal positions by computing the 3D coordinates of the geometrical shape of 3D object surfaces to align images [17,22]. When the image surface point clouds that are used for matching are widely spread in the oral cavity, the matching condition is favorable, and the whole accuracy of image registration can be increased [15,33]. In the present study, a significant correlation was found between the threshold of gray value factor and the number of remaining teeth on the registration accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of in vitro studies and systematic review, as well as multicenter clinical trials and randomized controlled trials, lead to the conclusion that using individual guides may be the best way to achieve elevated accuracy and remain in line with the treatment plan [7,8,[10][11][12][13][14]. However, limited surgical access especially in the distal area of the alveolar ridge with surgical guides intraorally, may be one of the most common challenges in using surgical guides [4,14].…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies show that users of CAD/CAM (Computer-aided design/Computer-aided manufacturing) surgical guides may experience problems with accuracy and repeatability of dental implantation procedures [2][3][4][5][6][7][8]. In the literature we can also find descriptions of a few problems with clinical application of guides (e.g., the guide fixation, its stability and limited mouth opening) [9,10]. Hence several surgical kits were introduced to help clinicians with proper implant positioning when a digital guide is not available.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, a misalignment of the STL/OBJ/PLY and DICOM files will not influence the surgical template fitting nor the sleeve position, but the final implant position will be different from the one observed in the bone. 17,46 Incorrect alignment of the merged files usually occurs when the number of common reference areas is insufficient. A lack of reference areas can be observed when the CBCT is performed with upper and lower teeth in occlusion or if metal artifacts are present.…”
Section: File Merging Processmentioning
confidence: 99%